Design And Development Of Microwave Transmitter For L-Band Scatterometer - Hii, William How Hsin (2006)
The most important reasons to use microwaves for remote sensing are its capability to penetrate clouds and rain and also independence of the sun as a source of illumination. Another reason for the use of microwave is that they are able to penetrate more deeply into vegetation than optical waves.